(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A topological index, also known as connectivity index, is a molecular structure descriptor calculated from a molecular graph of a chemical compound which characterizes its topology. Various topological indices are categorized based on their degree, distance and spectrum. In this study, the degree-based topological indices such as multiplicative geometric - arithmetic index ( ) (MGA index)isderived for various graphs